Pedro Penn - James , W. R.; Levy, Mrs.; James, Jonathan; James, William (Jamaica : [Publisher not identified], 1810)
Diagram shows parcel of land of 1810 acres. Also shown is land belonging to W. R. James and unsurveyed land called Pedro Bluff. On the other side, diagram shows land belonging to Mrs. Levy, Jonathan James, William James, Hopewell Plantation and New Mountain Settlement.
Keywords: Maps; St. Elizabeth (Jamaica) -- Maps; Pedro Bluff; Hopewell Plantation; New Mountain Settlement